Analysis of Ground Shear Strain (GSS) district Kawalu Tasikmalaya with HVSR method using microtremor data - Muhammad Reza Iswara; - Syafriani; Thomas Hardy (PILLAR OF PHYSICS, 2020)
Tasikmalaya is one of the areas affected by the earthquake. One of efforts to reduce the impact of the earthquake is by analyzing seismic hazard levels as one of the earthquake disaster mitigation efforst with the microtremor method. It can determine the amplification value and the dominan frequency. From the dominant frequency value and amplification can be calculated. Seismic vulnerabilities index (Kg) and value of Ground Shear Strain (GSS). From the value of vulnerability index (Kg) and ground shear strain (GSS) can be known how much the level of vulnerability of the area to earthquakes. Furthermore, a spatial description of the distribution map of the seismic vulnerability index (Kg) and the ground shear strain value distribution map (GSS) were made in Kawalu Subdistrict, Tasikmalaya City. The dominant frequency value is obtained from 0.6 Hz to 16.7 Hz. The seismic vulnerability index (Kg) from Kawalu Tasikmalaya ranges from 0.2 to 20, and the GSS value from the low is 0.17 in the village of Urug to the highest of 12.13 in the village of Leuwiliang. This allows Kawalu Subdistrict to get a deformation phenomenon such as liquefaction, landslides when earthquake.